Analisis Efektivitas Line Cubing 2 dengan Menggunakan Metode Overall Equipment Effectiveness di PT. BM - Dwiputra, Falsha Satria; Wahyudin, Wahyudin; Nugraha, Billy (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
PT. BM is a food seasoning company. One of its superior products is seasoning cubes. In the production process, seasoning cubes are found in cubing line 2. From the research results, cubing line 2 has problems that impact the high level of product defects and downtime. This research aims to analyze the OEE calculation online cubing 2 with the aim of increasing effectiveness and finding the root cause of the problem. Research methods involve problem identification, observation, literature study, data collection and analysis, discussion, recommendations for improvement, conclusions, and suggestions. The data was analyzed using OEE calculations and the root cause of the problem was identified using fishbone diagram analysis. Recommended improvements include setting brass as the standard bushing material, as well as carrying out preventive maintenance every 6 months. It is hoped that the implementation of these improvements can increase overall production effectiveness at PT. BM. Keywords: Availability Rate, Effectiveness, Overall Equipment Effectiveness, Performance Rate, Quality Rate.